Incidencia de la facturación electrónica en la recaudación fiscal en el pago de los contribuyentes del cantón Latacunga, en el periodo económico 2017. - Gavilánez Gavilánez, Edison Salomón (2018)
The present research project analyzed the incidence of electronic invoicing in the tax collection in the payment of consumers in Latacunga Canton, due to the ignorance of the contribution that this billing system offers in the tax collection. The purpose of this analysis was to determine the annual growth of taxpayers incorporated since the electronic invoicing regime was in effect, quantify and describe the payment of taxes made by customers before and after the validity of this regulation and finally verify the economic values collected by the Internal Revenue Service with the use of this billing system. The research methods were an applicative, descriptive, explanatory and deductive, because the present project has an inquiry with a quantitative approach, which information was collected in Internal Revenue Service, specifically of the tax obligations Withholding Tax, Income Tax, Value Added Tax and Special Consumption Tax. Since the main problem is the lack of knowledge about the incidence of electronic invoicing in the tax collection in the payment of consumers of the Canton Latacunga. This investigation verified the percentage increases of customers incorporated into the electronic invoicing regime, economic amounts collected before and after the implementation of this billing system and its variations and differences. The vital performance and efficiency of the management of electronic invoicing in tax collection and tax obligations carried out by taxpayers, thus considered an exemplary contribution to the tax collection function carried out by Internal Revenue Service. Based on the results obtained, it is essential that the SRI encourages customers to use this system; encouraging, innovation, efficiency, orienting in which competitiveness in commercial operations carried out by users must be achieved and with this achieve greater control in the collections received by the Treasury.